A3- and A2B-fluorocorroles: synthesis, X-ray characterization and antiviral activity evaluation against human cytomegalovirus infection. Issue 7 (13th July 2020) - Kappler-Gratias, Sandrine; Bucher, Léo; Desbois, Nicolas; Rousselin, Yoann; Bystricky, Kerstin; Gros, Claude P.; Gallardo, Franck
Abstract : New generation of anti hCMV molecules: 29 fluorinated corroles were studied for their antiviral activity evaluation against human cytomegalovirus infection and maximum activity is achieved for A2 B-corroles with SI above 400. Abstract : Twenty-nine fluorinated corroles were prepared, spectroscopically characterized, and studied for their antiviral activity against human cytomegalovirus infection. Six corroles were also fully characterized by X-ray crystallography giving insights on their geometrical features. The halogenated corroles reported herein exhibit significantly improved antiviral activity over their non-halogenated counterparts and over nitro-corrole analogs previously reported. Full activity of thirteen A3 -corroles is achieved with four fluorine atoms present on the meso -phenyl ring reaching a selectivity index above 300. The maximum activity is achieved for A2 B-corroles with selectivity indexes above 400. We thus demonstrate that the fluorocorrole is a highly potent platform to synthesize a new generation of anti hCMV molecules.